Toleran dan Bijaksana sebagai Sifat dan Kepribadian Guru dalam Perspektif Hadis - Nabila Ishmah Ramadhani; Yuliharti Yuliharti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This article aims to examine tolerance and wisdom as the nature and personality of the teacher in the perspective of hadith. This type of research is library research using data analysis techniques in the form of content analysis techniques. In this study, it was found that hadith narrated by Muslim from Mu'awiyah bin Al-Hakam As-Sulamiy explained about the prohibition of speaking in prayer and a teacher. The nature of an teacher exemplified by the Prophet Muhammad in the hadith when facing mistakes or violations committed by his students is gentle, tolerant and wise. Finally, it can be concluded that in the classroom and outside the classroom, in order to achieve a good teaching and learning process, teachers must be wise in dealing with the many opinions of students without intervening and blaming the opinions they express.